Towards a More Robust Financial Market: A Systematic Review of the Need for the Inception of Financial Derivatives Market in Bangladesh - Chowdhury, Tasnim Uddin; Bhuiya, Md. Monzur Morshed (ASEAN Journal of Management & Innovation, 2023)
Derivatives markets have become an integral part of the global financial landscape, enabling investors to manage risk, increase liquidity, and enhance price discovery. However, in Bangladesh, the concept derivatives is still in its nascent stage, and the lack of a well-developed market has hindered the growth of the financial sector. This paper presents a systematic review of the need for the creation of a derivatives market in Bangladesh. It analyzes the existing literature on the benefits of derivatives, their role in risk management, and their impact on market efficiency. It also examines the regulatory framework and the challenges facing the development of a derivatives market in Bangladesh. The paper suggests that the introduction of derivatives in Bangladesh can lead to a more robust and efficient financial market, with substantial benefits for both investors and the broader economy. However, to ensure the successful implementation of a derivatives market, policymakers must address the challenges associated with market infrastructure, investor education, and regulatory oversight. The paper provides insights for policymakers, academics, and practitioners interested in the development of financial markets in emerging economies.